2018
DOI: 10.1093/jas/sky233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dimethylglycine sodium salt supplementation on growth performance, hepatic antioxidant capacity, and mitochondria-related gene expression in weanling piglets born with low birth weight1

Abstract: Dimethylglycine sodium salt (DMG-Na), has exhibited excellent advantages in animal experiments and human health. The present study aimed to investigate the effects of dietary supplementation with 0.1% DMG-Na on the growth performance, hepatic antioxidant capacity and mRNA expression of mitochondria-related genes in low birth weight (LBW) piglets during weaning period. Sixteen piglets with normal birth weight (NBW) and sixteen LBW piglets were fed either a basal diet or a 0.1% DMG-Na supplemented diet from age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 57 publications
(64 reference statements)
4
23
0
Order By: Relevance
“…The increased ALP level in serum is related to the impairment of hepatic function resulting from liver cholestasis as well as the destroyed hepatocyte membrane. Similar observations have been reported in low-birth-weight piglets [61]. Also, liver dysfunction has been reported in IUGR infants [62].…”
Section: Discussionsupporting
confidence: 88%
“…The increased ALP level in serum is related to the impairment of hepatic function resulting from liver cholestasis as well as the destroyed hepatocyte membrane. Similar observations have been reported in low-birth-weight piglets [61]. Also, liver dysfunction has been reported in IUGR infants [62].…”
Section: Discussionsupporting
confidence: 88%
“…But the mRNA expression of SOD1 and GPx1 showed no significant differences compared with NBW piglets. Similarly, Feng [8] found that there is no difference in the mRNA expression of GPx1 and SOD1 in low body weight piglets and NBW piglets. Diets supplemented with DHA significantly increased the hepatic mRNA expression of HO-1 and Nrf2 in IUGR-affected piglets.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to the high rates of perinatal mortality, IUGR has recently been shown to increase the risk of oxidative damage and reports also suggest that fetal hepatocytes in infants affected by IUGR might be subjected to oxidative damage, which reduces their ability to detoxify the liver [6,7] The liver is the metabolic center of the body and plays an important role in the absorption and metabolism of nutrients. Many studies have reported that IUGR can cause severe oxidative damage to the liver of piglets [8,9]. Aydan [10] demonstrated that IUGR can destroy the dynamic balance of the oxidation-antioxidant system in the liver, which can cause damage to the body.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, IUGR piglets have been shown to be correlated with high morbidity and mortality, stunted growth, as well as poor carcass quality [1]. Great efforts have been made to minimize the negative effects of IUGR, and some investigations have shown that dietary nutrient supplementation can improve the survival and growth performance of IUGR piglets (e.g., mid-chain triglycerides [3], choline [4], arginine [5], and dimethylglycine sodium salt [6]). However, the underlying mechanisms of nutrient utilization in IUGR piglets were not well defined, and it is difficult to take effective measures to maximize the performance of IUGR piglets.…”
Section: Introductionmentioning
confidence: 99%